Occupational preferences of people with hearing disabilities - deaf and hard of hearing who are enrolled in university studies (according to Holland’s theory) and their relationship to some variables - Sallam, Ahmed Mahmoud (Al-Adab Journal, 2023)
The current study aims to explore the occupational preferences of people with hearing impairments at the University of Sharjah and applicants to study according to the Netherlands theory. The sample consisted of (18) male and female students, divided into (9) males and (9) females. The researcher used the Vocational Preference Inventory (VPI) tool. The study concluded that the occupational preferences of the sample members were arranged so that the traditional style and then the realistic style are the most preferred occupational styles for people with hearing disabilities in the current study, and the explorer style comes as the least preferred occupational style for people with hearing disabilities. they. There are also differences between occupational preferences according to the gender variable (males and females), as the realistic style is the most preferred occupational style among male sample members, followed by the traditional style, and the explorer style comes at the end of the hierarchy of occupational preferences for them, while the traditional style is the most preference. Female occupational style, followed by social and adventurous style, and pragmatic style come at the end of the hierarchy of female occupational preferences. By comparing the number of jobs chosen by him (male and female), it turns out that females lack awareness of available job opportunities and can get into them, in contrast to the opportunities that males can enter. However, the educational opportunities available to some extent correspond to the occupational preferences of females and do not correspond to the occupational preferences of males.